Quantitative in vitro phenotyping and prediction of drug interaction potential of CYP2B6 substrates as victims. (3rd July 2018) - Palacharla, Raghava Choudary; Nirogi, Ramakrishna; Uthukam, Venkatesham; Manoharan, Arunkumar; Ponnamaneni, Ranjith Kumar; Kalaikadhiban, Ilayaraja
Abstract: 1. Determination of fm, CYP for a compound is critical to assess the potential risk of a drug candidate as a victim of DDI. Several compounds are identified as CYP2B6 substrates, but the fm, CYP2B6 values are not determined quantitatively. 2. Two methods of reaction phenotyping, the chemical inhibition method and metabolism in rCYP enzymes, were used to determine the relative contributions of the enzymes. Chemical inhibition method was also conducted in the presence of BSA (0.5% w/v). 3. The results confirm with the earlier studies concerning the identity of the CYP2B6 enzyme. The fm, CYP2B6 values for artemisinin, bupropion, clopidogrel, ketamine, selegiline, sertraline and ticlopidine were 0.24, 0.28, 0.15, 0.45, 0.46, 0.42 and 0.54, respectively, in HLM determined by chemical inhibition method. The fm, CYP2B6 values for artemisinin, bupropion, clopidogrel, ketamine, selegiline, sertraline and ticlopidine were 0.46, 0.17, 0.15, 0.60, 0.51, 0.66 and 0.77, respectively, in HLM determined by chemical inhibition method in the presence of BSA (0.5% w/v). 4. Bupropion metabolism is majorly mediated by CYP2C19 (0.41) with a minor contribution from CYP2B6 (0.16) in the presence of BSA. Ticlopidine is a time-dependent inhibitor of both CYP2B6 and CYP2C19 that can inhibit the bupropion metabolism by 50–60%.